The Effect of GC on The Students’ Writing Skills at SMA Swasta Dwiwarna Medan - Nandheni, Havina (ELT (English Language Teaching Prima Journal), 2022)
The research aim is to find the effectiveness out of the use of the GC Application on the students’ writing skills at grade X and grade XI of SMA Swasta Dwiwarna Medan. To carry out this research, the writers used quantitative medthod.Based on the research findings, the writers concluded thatit is very effective using the GC Application is than using the conventional teaching strategy in teaching writing skills toward the students who were from grade X and grade XI of SMA Swasta Swasta Dwiwarna Medan. From the data, it was known that 79.33 was the mean scores of students after using GC Application who were from the experimental class. Then it was known that 3,628 were the Standard Deviation after the use of the GC Application in the experimental class with 18 students. Meanwhile it was known that 63.72 were the mean scores after using conventional teaching strategy and 3,108 were the Standard Deviation from the control class with 15 students. Mean scores in the experimental class were increased 10.60 points. From the control class, the mean scores were increased 6.11 points. From the test of normality, the writers can conclude that 0.637 was the result in the post-test after the implementation of the GC Application in the experimental class and 0.234 was the result of normality test by using the conventional teaching strategy in the control class.   Keywords: The Effect, GC Application, Writing Skills, Narrative Text